High‐Voltage, Highly Reversible Sodium Batteries Enabled by Fluorine‐Rich Electrode/Electrolyte Interphases. Issue 6 (24th April 2022) - Guo, Xu‐Feng; Yang, Zhuo; Zhu, Yan‐Fang; Liu, Xiao‐Hao; He, Xiang‐Xi; Li, Li; Qiao, Yun; Chou, Shu‐Lei
Abstract: High energy density and long‐term cycling stability are crucial factors for the commercialization of sodium batteries in large scale. In this regard, cathode materials that can operate at high voltage have attracted great interest owing to their high energy density. However, traditional electrolytes cannot be used in high‐voltage sodium batteries due to their limited oxidative stability. Therefore, there is a great challenge to develop appropriate electrolytes for high‐voltage cathode materials. Herein, a diluted fluoroethylene carbonate (FEC)‐based electrolyte (1 m NaPF6 in FEC/DMC = 2/8 by volume) is designed for Na4 Co3 (PO4 )2 P2 O7 (NCPP) cathode with a high operation voltage of 4.7 V to achieve superior electrochemical performance with a capacity retention of 90.10% after 500 cycles at 0.5 C and capacity retention of 89.99% after 1000 cycles at 1 C. The excellent electrochemical performance of the NCPP||Na cells can be attributed to the formation of inorganic and robust NaF‐rich cathode electrolyte interphase and F‐rich solid electrolyte interface on high voltage NCPP cathode and Na metal anode, respectively. This work points out a very promising strategy to develop high‐voltage sodium batteries toward practical applications. Abstract : A diluted fluoroethylene carbonate (FEC)‐based electrolyte is utilized in 4.7 V‐class Na4 Co3 (PO4 )2 P2 O7 ||Na (NCPP||Na) cell, which performs a superior electrochemical performance with a capacity retention of 89.99% after 1000 cycles at 1 C. This is attributed to the formation of inorganic and robust NaF‐rich cathode electrolyte interphase on NCPP cathode and F‐rich solid electrolyte interface on Na anode.